Innovative Utilization of the Moodle in Postgraduate ODL Courses at Universiti Sains Islam Malaysia - Zainuddin, N; Idrus, R; Jamal, AFM (Acad Conferences Ltd, 2024)
This article promotes the use of Moodle as a suitable platform to support the postgraduate open and distance learning (ODL) courses offered by Universiti Sains Islam Malaysia (USIM). Many USIM postgraduate students who take obligatory courses (e.g., research methodology and data analysis) are taught at different venues to facilitate students' access to high education and enhance quality of lifelong learning. Managing this complex teaching network has called for the adaptation of Moodle platform. This approach meets two relevant requirements, (a) to ensure consistency, compliance, and quality of teaching, (b) to reduce educational costs, which largely depend on the number of peripheral venues for teaching activities. This article analyses the functionalities of Moodle platform and its use among USIM postgraduate students. The data was collected based on content analysis, one non-structured interview with the responsible of the Moodle from USIM and a questionnaire applied to 18 students. The results show that despite Moodle has a great potential, mainly used as a repository of materials. Moreover, students recognize the importance of the use of other functionalities of this platform in order to promote the success of the teaching and learning process.